PENGARUH PEMAHAMAN SISTEM AKUNTANSI KEUANGAN DAERAH DAN AKTIVITAS PENGENDALIAN TERHADAP AKUNTABILITAS KEUANGAN PADA PEMERINTAH KABUPATEN GIANYAR - Sang Ayu Putu Arie Indraswarawati; Cokorda Gde Bayu Putra; I Putu Teresna Jaya Manggala (UNHI Press, 2020)
Research conducted aims to get a clear of financial accountability seen from the understanding of the financialaccounting system in the Gianyar Regency Government, getting an idea of financial accountability seen from the activity control, try to give suggestions that can help the Gianyar Regency Government in solving the problems faced, especially the problems studied, namely the influence of understanding the regional financial accounting system and control activities on financial accountability in Gianyar Regency Government. The result of overall lregression analysis indicate that 66,2% of the independent variables can be explained by the depemdent variable, while the remaining 33,8% is explained by other factors or variable,